X 6 y 2 6 y 2 y 1 12 2 y 2 y 1 12

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: tute this into the second equation. 2 x + 3 ( 3x - 7 ) = 1 This is an equation in x that we can solve so let’s do that. 2 x + 9 x - 21 = 1 11x = 22 x=2 So, there is the x portion of the solution. Finally, do NOT forget to go back and find the y portion of the solution. This is one of the more common mistakes students make in solving systems. To so this we can either plug the x value into one of the original equations and solve for y or we can just plug it into our substitution that we found in the first step. That will be easier so let’s do that. y = 3 x - 7 = 3 ( 2 ) - 7 = -1 So, the solution is x = 2 and y = -1 as we noted above. [Return to Problems] (b) 5x + 4 y = 1 3x - 6 y = 2 With this system we aren’t going to be able to completely avoid fractions. However, it looks like if we solve the second equation for x we can minimize them. Here is that work. 3x = 6 y + 2 2 x = 2y + 3 Now, substitute this into the first equation and solve the resulting equation for y. 2ö æ 5ç 2 y + ÷ + 4 y = 1 3ø è 10 10 y + + 4...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online